Wetlands and Sustainable Livelihoods: Alternative Means of Water Security in the Drought Season Within the Rural Communities in Limpopo Province of South Africa - Mabule, P. N.; Baloyi, D. (International Conference on Public Administration and Development Alternative (IPADA), 2019)
This paper argues that wetlands conservation is a viable tool to sustain livelihoods and secure water. South Africa climate is characterised by periods of La Nina and El Nina, unfortunately, the country is experiencing the El Nina season (period of dry spells) and the communities at the peripheries are affected mostly by these phenomena. As the drought continues to devastate most of the country as recurrent characteristics of the climate change, livelihoods of ordinary South Africans are threatened. Therefore, with highly constrained freshwater resources, weather extremes such as drought imposed by climate variability and change affect the limited water. The conservation of wetlands in South Africa can be a tool for sustainable livelihoods and ensure water security if they are well maintained and preserved. Evidently, since the drought, the agricultural sector growth has realised a decline of 12,6%, with most of the rural communities relying on the agricultural sector for food, farming and as a source of employment. Groundwater is much slower to be affected by drought than surface water and worldwide groundwater has proved to be a good buffer against drought, despite these enormous benefits wetlands continue to be lost and degraded at an alarming rate due to the problems of pollution, agricultural expansion, and urbanisation and is vulnerable to development. This paper concludes that the loss and degradation of wetlands undermine the sustainability of the development that is often responsible for their demis
Article published in the 4th Annual International Conference on Public Administration and Development Alternatives
Keywords: Conservation; Drought; El Nina; La Nina; Livelihoods; Sustainable; Wetland; Freshwater ecology--South Africa